Pengembangan Modul Digital Menggunakan Flip PDF Professional Pada Pembelajaran Tematik Terpadu di Kelas V Sekolah Dasar - Khairiyah, Arifatul; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This research is motivated by the lack of variety of learning resources used in schools and not fully utilizing technology in its development. The aim of the research is to develop valid and practical digital-based modules using the Flip PDF Professional application to support the successful implementation of "Integrated Thematic Learning" in class V SD. This type of research is a 4D model development research (R&D). The 4D model has 4 stages: definition, design, development, and deployment. After the digital-based module has been designed, validity and practicality tests are carried out. The results of the validity test came from 91.7% learning material experts, 93.7% linguists and 95% media experts. The average validation score is 93.47% with a very valid category. The practicality test was carried out by giving questionnaires to teachers in trial schools 92.8%, students 94.8%, research school teachers 96.4%, and students 94.1% in the very practical category. Thus, the results of the study indicate that the digital-based module teaching materials developed using the Flip PDF Professional application are very feasible and practical to use in fifth-grade elementary schools.